2018
DOI: 10.3389/fimmu.2018.01428
|View full text |Cite
|
Sign up to set email alerts
|

The Ebola-Glycoprotein Modulates the Function of Natural Killer Cells

Abstract: The Ebola virus (EBOV) uses evasion mechanisms that directly interfere with host T-cell antiviral responses. By steric shielding of human leukocyte antigen class-1, the Ebola glycoprotein (GP) blocks interaction with T-cell receptors (TCRs), thus rendering T cells unable to attack virus-infected cells. It is likely that this mechanism could promote increased natural killer (NK) cell activity against GP-expressing cells by preventing the engagement of NK inhibitory receptors; however, we found that primary huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 71 publications
4
26
0
Order By: Relevance
“…Here, we observed a lower binding of NKG2D-Fc chimeric soluble receptors to EBOV-GP transfected HEK 293 cells corresponding to reduced expression of MICA/B (Fig. 6b, bottom), as has been reported before (115). Interestingly, we reported previously for Vaccinia virus (VV)-infected HeLa cells that the cumulative expression of NKG2D ligands (MICA, MICB, ULBP1, ULBP2, ULBP3, and ULBP4) was identical to that in noninfected cells, as detected with NKG2D-Fc (59,141,142).…”
Section: Ebov-gp Protects Hek-293 Cells From Lysis By Polyclonal Nk Csupporting
confidence: 88%
See 1 more Smart Citation
“…Here, we observed a lower binding of NKG2D-Fc chimeric soluble receptors to EBOV-GP transfected HEK 293 cells corresponding to reduced expression of MICA/B (Fig. 6b, bottom), as has been reported before (115). Interestingly, we reported previously for Vaccinia virus (VV)-infected HeLa cells that the cumulative expression of NKG2D ligands (MICA, MICB, ULBP1, ULBP2, ULBP3, and ULBP4) was identical to that in noninfected cells, as detected with NKG2D-Fc (59,141,142).…”
Section: Ebov-gp Protects Hek-293 Cells From Lysis By Polyclonal Nk Csupporting
confidence: 88%
“…6a). In addition, we observed a lower binding of NKG2D-Fc chimeric soluble receptors to EBOV-GP transfected HEK 293 cells ( Fig.6b), which indicates a reduction of its ligands MIC-A/B, as it has been shown before (115). Altogether, these data suggest that a by EBOV-GP reduced stimulation of NKG2D, together with the recruitment of Siglec-ligands on the surface of infected cells, may lead to a suppressive state of effector cells (Fig.…”
Section: Psgl-1 Cd24 Cd44 Dr3 and Ebola-gp Are Receptors For Selecsupporting
confidence: 80%
“…We and others have shown that expression of EBOV-GP shields cell membrane HLA-I from recognition by antibodies or by TCR (Ignatiev et al, 2000;Geisbert et al, 2003;Reed et al, 2004). We then showed that expression of EBOV-GP on target cells also shields ligands to activating NK receptors (Edri et al, 2018). The GP1 fragment of the GP was mediating this shielding since both trypsin and DTT treatments of the cells that remove the GP1 (enzymatically and chemically, respectively) abolished the shielding (Edri et al, 2018).…”
Section: N-glycosylation Of Mld and Gcd Domains Of Gp1 Is Involved Inmentioning
confidence: 82%
“…We then showed that expression of EBOV-GP on target cells also shields ligands to activating NK receptors (Edri et al, 2018). The GP1 fragment of the GP was mediating this shielding since both trypsin and DTT treatments of the cells that remove the GP1 (enzymatically and chemically, respectively) abolished the shielding (Edri et al, 2018). We now investigated whether the N-glycosylation of the GP1 is the major factor mediating this shielding.…”
Section: N-glycosylation Of Mld and Gcd Domains Of Gp1 Is Involved Inmentioning
confidence: 98%
See 1 more Smart Citation